"A gaol is not like a new post office or railway station": Invercargill reformatory prison - McCarthy, Christine (Architectural History Aotearoa, 2019)
The years of the first decade of the twentieth-century in New Zealand saw the building and development of New Zealand’s first reformatory prison in Invercargill. This paper explores the historical and legislative context of this building.